Higher education digital transformation implementation in Indonesia during the COVID-19 pandemic - Taufan Teguh Akbari; Rizky Ridho Pratomo (Universitas Padjadjaran, 2022)
The pandemic is forcing universities to carry out digital transformation simultaneously. However, the pandemic opened Pandora’s box revealing the fundamental weaknesses of universities that make them unprepared to adapt to changing times. However, the pandemic can be an opportunity to transform the entire workforce in universities so that their existence remains relevant. The critical factor in this transformation is the leader. Today’s leaders must change from traditional to digital. Digital leaders can be a catalyst for change to oversee digital transformation in universities. Therefore, this study intends to explain how the implementation of digital leadership in universities in Indonesia, especially since the world has been hit by a pandemic. The author uses the literature study method and interviews stakeholders in universities. The author finds that three fundamental challenges must be overcome: culture and mindset, human resource competence, and infrastructure. Higher education leaders must resolve these three challenges to ensure that digital transformation runs smoothly. The author argues that universities are still relevant to producing quality human resources and abilities according to the times. To maintain the relevance and role of universities, leaders need to implement changes holistically, starting by creating a holistic grand design, increasing human resource competencies, infrastructure development, developing a new mindset, creating progressive culture, to organizational restructuring.